Common morbidity and utilization rate of the university health centre, International Islamic University, Malaysia, (Kuantan campus) in 2010 - Tin, Myo Han; Abdullah, Fa’iza; Md Aris, Mohd Aznan (2012)

(untitled)
University Health Centre, International Islamic University, (UHC-IIUM), Kuantan campus is a primary care clinic for its community, students, staff and their dependents. Common morbidity and utilization rate of the clinic need to be analyzed to know current practices environment for further planning to provide quality primary health care services in line with vision of the clinic.